Non-coding RNA and pseudogenes in neurodegenerative diseases: “The (un)Usual Suspects” - Costa, Valerio; Esposito, Roberta; Aprile, Marianna; Ciccodicola, Alfredo (Frontiers in Genetics, 2012)
Neurodegenerative disorders and cancer are severe diseases threatening human health. The glaring differences between neurons and cancer cells mask the processes involved in their pathogenesis. Defects in cell cycle, DNA repair and cell differentiation can determine unlimited proliferation in cancer, or conversely, compromise neuronal plasticity, leading to cell death and neurodegeneration. Alteration in regulatory networks affecting gene expression contribute to human diseases' onset, including neurodegenerative disorders, and deregulation of non-coding RNAs - particularly microRNAs - is supposed to have a significant impact. Recently, competitive endogenous RNAs - acting as sponges - have been identified in cancer, indicating a new and intricate regulatory network. Given that neurodegenerative disorders and cancer share altered genes and pathways, and considering the emerging role of microRNAs in neurogenesis, we hypothesize competitive endogenous RNAs may be implicated in neurodegenerative diseases. Here we propose, and computationally predict, such regulatory mechanism may be shared between the diseases. It is predictable that similar regulation occurs in other complex diseases, and further investigation is needed.